2023
DOI: 10.3390/jcm12051759
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Role of Cognitive Reserve in Mild Cognitive Impairment: A Systematic Review

Abstract: Cognitive reserve (CR) represents the ability to optimize performance and functioning to cope with brain damage or disease. CR reflects the capability to adaptively and flexibly use cognitive processes and brain networks to compensate for the deterioration typical of aging. Several studies have investigated the potential role of CR in aging, especially from the perspective of preventing and protecting against dementia and Mild Cognitive Impairment (MCI). This systematic literature review aimed to investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…During the pandemic, subjects' performance on both ACE-R and the MMSE did not indicate the presence of MCI (i.e. 24 ), as all subjects scored above the regulatory cut-off and did not report SCD 10 , which was also assessed with the Cognitive Function Instrument (CFI 38 ). Their performance was above the reference cut-off on the following tests: MoCA (100%), RMT—15 immediate words (97%), RMT—15 delayed words (97%), TMT—Part A (100%), TMT—Part B (100%), TMT B-A (100%), and TT (97%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the pandemic, subjects' performance on both ACE-R and the MMSE did not indicate the presence of MCI (i.e. 24 ), as all subjects scored above the regulatory cut-off and did not report SCD 10 , which was also assessed with the Cognitive Function Instrument (CFI 38 ). Their performance was above the reference cut-off on the following tests: MoCA (100%), RMT—15 immediate words (97%), RMT—15 delayed words (97%), TMT—Part A (100%), TMT—Part B (100%), TMT B-A (100%), and TT (97%).…”
Section: Resultsmentioning
confidence: 99%
“…It improves cognitive function in healthy aging subjects; in particular, CR has been associated with global cognition 21 and has been reported to enhance executive function and attention 22 , 23 . CR has also been shown to be protective against brain damage and dementia 24 , slowing the cognitive aging process or reducing the risk of psychiatric disorders 25 . Indeed, CR can be altered or improved by cognitive, mental, and physical stimulation activities 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, future research should overcome these issues, extending the number and type of tests to be administered. Moreover, to favor the generalizability of the current findings, the study must be replicated both with larger samples of cognitively healthy respondents recruited elsewhere and participants exhibiting Mild Cognitive Impairment, since CR and physical reserve may be fundamental as protective factors to contrast the impact of cognitive decline and the occurrence of dementia in late lifespan (e.g., Bherer et al, 2013; Corbo et al, 2023; Fastame et al, 2022a). Finally, future longitudinal research is necessary to clarify the role played by the developmental factors in the relationship among CR, physical reserve, and cognition in late adulthood.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, a recent longitudinal study showed that individuals who devoted their time to cognitively stimulating leisure activities (e.g., reading, traveling, learning a second language) in the late-life stage (i.e., over 65 years of age) and who were regularly engaged with the others in young adulthood (i.e., 13–29 years of age), were less exposed to cognitive decline at the 6-year follow-up (Litkouhi et al, 2023). Besides, it has also been documented that educational attainment (Godinho et al, 2022) and job occupation play (Kim et al, 2021) a crucial role as protective factors against cognitive decline in healthy aging and serve as compensatory resources in individuals exhibiting Mild Cognitive Impairment (for a review, see Corbo et al, 2023). Extending this, Calatayud et al (2022) found that older individuals who performed intellectually demanding jobs, later exhibited better cognitive functioning but poorer functional development of basic and instrumental activities of daily life.…”
Section: Introductionmentioning
confidence: 99%
“…These impairments could worsen MCI patients' performances in many domains, not only related to cognitive functioning, and can be affected by many impaired aspects in elderly people, such as sleep quality and mental health [61,62]. Therefore, it is extremely important to investigate these aspects further, also considering some relevant aspects, such as cognitive reserve [63], in order to develop psychological interventions to improve memory of the past.…”
Section: Discussionmentioning
confidence: 99%